Educational CornerAdjuvant vaginal brachytherapy as a part of management in early endometrial cancer - Kellas-Ślęczka, Sylwia; Wojcieszek, Piotr; Białas, Brygida (Journal of Contemporary Brachytherapy, 2012)
Endometrial cancer is the most frequent cancer of female genital tract. Metro- and menorrhagia or postmenopausal bleeding results in its early presentation. It allows radical treatment. However, controversies remain on surgery coverage or adjuvant therapies in early endometrial women cancer. Optimal management should minimize intervention instead of aggressive approach, as showed by recent studies. There is a role for brachytherapy as an adjuvant irradiation. Crucial publications including PORTEC-1, GOG 99, MRC ASTEC, ASTEC/EN.5, PORTEC-2 or Italian lymphadenectomy trial are discussed. Moreover, there is attention paid on adjuvant vaginal brachytherapy analyses for the past fifteen years.